FEED CONSUMPTION AND DIGESTIBILITY OF MALE BALINES DUCK THAT GIVEN INDIGOFERA (I.zollingeriana) LEAF JUICE - L. M., Tarigan; Puspani, E.; Warmadewi, D. A. (Jurnal Peternakan Tropika, 2024)
Utilizations of indigofera leaves is a plant that contains flavonoids, saponins and tannins.  This study aims to determine the effect of giving indigofera leaf juice on feed consumption and digestibility and has been carried out for eight weeks at Teaching Farm Faculty of Animal Husandry, Udayana University, Bali.  The design of this study is a completely randomized design (CRD), wich consist 4 treatments and 5 replications, each replications consist of 6 ducks, so there are 120 male balines ducks.  The four treatments were the level of indigofera leaf juice is P 0 (control), P 1 (2%), P 2 (4%) and P 3 (6%).  Variables observed is dry matter consumption, faecal dry matter, dry matter digestibility, organic matter consumption, faecal organic matter and organic matter digestibility.  The data obtained were analyzed using analyze of variance, if there were significant differences (P<0,05) then analyze was continued with Duncan’s multiple distance test. The result showed that the administration of indigofera leaf juice has significant (P<0,05) increased the consumption and digestibility of dry matter and organic matter.  Based on the results of study it can be concluded that administration 2-6% indigofera leaf juice can increase the consumption and digestibility of dry matter and organic matter.